1987
DOI: 10.1038/clpt.1987.43
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic exercise-induced increase in lymphocyte beta-2-adrenoceptors: Abnormality in essential hypertension and its correction by antihypertensives

Abstract: We compared the effects of acute stimulation of sympathetic activity by dynamic exercise on a bicycle on lymphocyte beta 2-adrenoceptor density and 10 mumol/L (-)-isoprenaline-evoked lymphocyte cyclic adenosine monophosphate increases in normotensive volunteers with those in patients with essential hypertension. In normotensive subjects exercise increased lymphocyte beta 2-adrenoceptors by about 100%. This effect seems to be a beta 2-dependent process, since it is prevented by propranolol (5 mg administered in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…5 We also found that lymphocyte ␤ 2 -adrenoceptor density was increased in hypertensive patients, as previously described, [9][10][11] while ␤ 2 -adrenoceptor response was similar in both groups. A novel and interesting finding resulting from this study was that LVMI showed an inverse relationship with both lymphocyte ␤ 2 -adrenoceptor density and response in hypertensive patients only, suggesting that ␤-adrenoceptors are down-regulated in hypertensive patients with left ventricular hypertrophy.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…5 We also found that lymphocyte ␤ 2 -adrenoceptor density was increased in hypertensive patients, as previously described, [9][10][11] while ␤ 2 -adrenoceptor response was similar in both groups. A novel and interesting finding resulting from this study was that LVMI showed an inverse relationship with both lymphocyte ␤ 2 -adrenoceptor density and response in hypertensive patients only, suggesting that ␤-adrenoceptors are down-regulated in hypertensive patients with left ventricular hypertrophy.…”
Section: Discussionsupporting
confidence: 71%
“…Journal of Human Hypertension (2000) 14, [17][18][19][20][21] both in animal models of hypertension and hypertensive patients. 7,8 On the other hand, several abnormalities have been reported in lymphocyte ␤ 2 -adrenoceptor characteristics in hypertensive patients, [9][10][11] suggesting that the same occurs in target organs, such as the heart. Interestingly, a decreased lymphocyte ␤ 2 -adrenoceptor function has been reported in essential hypertensive patients with LVH.…”
Section: Introductionmentioning
confidence: 99%
“…fl-AR translocated in sarcolemmal membranes just after exercise returned to the intracellular sites within at least 15 min afterwards . Acute exercise-induced up-regulation of human lymphocyte f3-AR is also followed by a return to pre-exercise level after supine rest for 25-60 min (BUTLER et al , 1983;BRODDE et al, 1984BRODDE et al, , 1987BRODDE et al, , 1988MAKI et a1.,1988). Similarly, in in vitro study , LIMAS and LIMAS (1984) reported that cell surface fl-AR loss of intact cardiac myocytes, induced by preincubation with isoproterenol, could be almost restored to control level at only 20 min after removal of isoproterenol from incubation medium in rat .…”
Section: Other Determinationsmentioning
confidence: 99%
“…An acute or chronic exposure to exercise might then be expected as an useful model for investigation of in vivo /3-AR adaptation under a "physiological" condition. Indeed the data have been accumulated that the density of human lymphocyte fl-AR increases immediately after a single exposure to strenuous exercise (BUTLER et al, 1983;BRODDE et al, 1984BRODDE et al, , 1987BRODDE et al, , 1988FREY et al, 1987;MAKI et al, 1988) with subsequent desensitization of fl-AR (BUTLER et al, 1983). Chronic exposure to exercise leads to a decreased lymphocyte /3-AR density (BUTLER et al, 1982).…”
mentioning
confidence: 99%
“…Especially, the number of b-AR and the responsiveness of b-AR to an agonist (3,28), and the content of stimulatory guanine nucleotide binding protein (18) in human lymphocytes, are significantly correlated with those in the myocardium. Dynamic exercise induces increases in b-AR number in human lymphocytes (2,5,13,15), and identical increases in b-AR number have been demonstrated in the myocardium of the rat (19). For this reason, lymphocytes derived from peripheral blood are often utilized as a model for determining the effects of acute dynamic exercise on the b-AR system.…”
mentioning
confidence: 99%